Doxycycline Drug Release Property of Glutaraldehyde Crosslinked Hydrogel - Kavish P; Kalpana R (Wolters Kluwer Medknow Publications, 2024)
Delayed wound healing is one of the most common problems associated with diabetic patients. There are several factors associated with delayed wound healing. It has been observed that if not cured the wound healing takes a long time. This is the reason that researchers are engaged in developing sustainable, biodegradable, biocompatible, and effective wound-healing dressings. However, it has been observed that the traditional wound-healing bandages have drawbacks such as allergies and less efficiency in the absorption of wound exudate. To fill the gap, hydrogels have been developed recently which have higher absorption capacity. In addition, they pose slow drug release properties. Therefore, the present study was conducted to prepare an effective and promising hydrogel that has high drug absorption and release properties.